Two new species in the mycophagous genus Pocadius Erichson, 1843 from China (Coleoptera: Nitidulidae: Nitidulinae) - Chen, Xiaoxiao; Huang, Min (Zootaxa, 2020)
Two new Pocadius species, P. tenebrosus sp. nov. and P. zhangjiajieensis sp. nov., are described and illustrated from southwestern and south-central China. Diagnostic characters of the new species and related species are discussed.